Listed companies' income tax planning and earnings management: Based on China's capital market - Nanwei Hu; Qiang Cao; Lulu Zheng (Journal of Industrial Engineering and Management (JIEM), 2015)
Purpose: The Ministry of Finance issued the new China accounting standards on February 15, 2006(CAS2006), which requires the listed companies to use the balance sheet liability method for the income tax accounting. Thus, it gives us an opportunity to investigate the earnings management of listed companies from the perspective of income tax. Under the balance sheet liability method, our researches just try to investigate the relationship between the listed companies' income tax planning and earnings management. Design/methodology/approach: Our research approach combines theoretical analysis and empirical analysis. This paper first makes a deep theoretical analysis on the listed companies' choice between pretax earnings management activities and earnings management activities, and then we exemplify our theory. Next, we come up with two hypotheses based on the theoretical analysis, build up a restatement model and conduct the empirical examination. The empirical analysis employs the method of descriptive statistics and logistic regression. Findings: When engaging in earnings management, listed companies will trade off conforming and nonconforming earnings management from the perspective of income tax cost. We find that managers' motivations and purposes will influence the choice. When the company has motivations to turn losses into gains and has motivations to avoid penalty cost associated with fraud being found, the company prefers to employ more conforming earnings management strategies. Research limitations/implications: The limitation in our research is as follows. First, we mainly focus on the conforming and nonconforming earnings management when the listed companies restate their financial statements. However after the issue of CAS2006, many listed companies still not disclose income tax account, which restrict our sample. Second, without the acquisition of private companies' data, our empirical results may have some errors. We will solve these problems in our future study. ractical/social implications: First of all, our research provides new perspective and theoretical evidence for exploring the listed companies' choice of conforming and nonconforming earnings management. Meanwhile, our results are helpful for regulators to strengthen the administration of listed companies' restatement. Finally, our results will help us to deeply understand the impact of the accounting processes of income tax under the balance sheet liability method on the listed companies. Originality/value: So far, there are few studies discussing the choice of earnings management strategies and how different purposes and motivations affect the choice from the perspective of income tax. The issue of CAS2006 offers an opportunity for this research. This paper use restatement as sample to investigate the choice of conforming earnings management and nonconforming earnings management under different motivations and purposes for the first time.
Keywords: 650; earnings management; book-tax differences; deferred tax expense